Exercise testing in heart failure with preserved ejection fraction: an appraisal through diagnosis, pathophysiology and therapy – A clinical consensus statement of the Heart Failure Association and European Association of Preventive Cardiology of the European Society of Cardiology - Guazzi, Marco; Wilhelm, Matthias; Halle, Martin; Van Craenenbroeck, Emeline; Kemps, Hareld; De Boer, Rudolph A.; Coats, Andrew J. S.; Lund, Lars; Mancini, Donna; Borlaug, Barry; Filippatos, Gerasimos; Pieske, Burkert (European Journal of Heart Failure, 2022)
Patients with heart failure with preserved ejection fraction (HFpEF) universally complain of exercise intolerance and dyspnoea as key clinical correlates. Cardiac as well as extracardiac components play a role for the limited exercise capacity, including an impaired cardiac and peripheral vascular reserve, a limitation in mechanical ventilation and/or gas exchange with reduced pulmonary vascular reserve, skeletal muscle dysfunction and iron deficiency/anaemia. Although most of these components can be differentiated and quantified through gas exchange analysis by cardiopulmonary exercise testing (CPET), the information provided by objective measures of exercise performance has not been systematically considered in the recent algorithms/scores for HFpEF diagnosis, by neither European nor US groups. The current clinical consensus statement by the Heart Failure Association (HFA) and European Association of Preventive Cardiology (EAPC) of the European Society of Cardiology (ESC) aims at outlining the role of exercise testing and its pathophysiological, clinical and prognostic insights, addressing the implications of a thorough functional evaluation from the diagnostic algorithm to the pathophysiology and treatment perspectives of HFpEF. Along with these goals, we provide a specific analysis of the evidence that CPET is the standard for assessing, quantifying, and differentiating the origin of dyspnoea and exercise impairment and even more so when combined with echocardiography and/or invasive haemodynamic evaluation. This will lead to improved quality of diagnosis when applying the proposed scores and may also help to implement the progressive characterization of the specific HFpEF phenotypes, a critical step toward the delivery of phenotype-specific treatments.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Exercise; Functional limitation; Gas exchange analysis; HFpEF